Arthroscopic confirmation of femoral button deployment avoids post-operative X-ray in ACL reconstruction. Issue 2 (3rd April 2021) - Matassi, Fabrizio; Sani, Giacomo; Innocenti, Matteo; Giabbani, Niccolò; Civinini, Roberto
ABSTRACT: Background: Anterior cruciate ligament reconstruction (ACLR) with cortical fixation adjustable-loop devices are associated with high potential risk of button malpositioning or interposition of the soft tissue between lateral femoral cortex and the button. Surgeons usually use X-rays to check and avoid button malposition and soft tissue interposition. Arthroscopic visualization of button position through the lateral gutter has been described. With this technique, it is possible for identification and correction of femoral button malalignment in the setting of soft tissue interposition and it could avoid the use of post-operative X-ray. Methods: A total of 193 ACLR were included and patients were randomized into two groups. The first series (Group A) of 112 patients who sustained an ACLR with post-operative X-ray to assess the position of the femoral button and the second series (Group B) of 81 patients who sustained an ACLR with an arthroscopic exploration of the button followed by post-operative X-ray. Results: On the post-operative radiographs, tissue interposition between the button and femoral cortex was found in nine cases of 112 in Group A (8%) and in zero case of 81 in Group B (0%). In six cases (7, 4%) in Group B, there was a soft tissue interposition between the button and femoral cortex as visualized by arthroscopic confirmation and before post-operative X-ray; in all these cases, the soft tissue was removed, and the button was in contact with the bone in all X-ray made in the Group B. Conclusions: This technique allows for identification and correction of femoral button malalignment in the setting of soft tissue interposition and reduces the use of post-operative X-ray.